Family Independence in Implementing Family Health Tasks to Reduce the Risk of Fall in East Pentadio Village, Gorontalo Regency - Rona Febriyona; Pipin Yunus; Nadia M. Laukum; Deisy Cintiya Ismail; Rian Y. Kune (Journal of Universal Community Empowerment Provision, 2021)
Independence is a condition in which a person who has the will and ability tries to fulfill the demands of his life in a legal, reasonable and responsible manner for everything he does. The family has a very big role in the safety of the elderly, especially in preventing falls. The purpose of this study is that the public can find out the importance of family independence in carrying out family health tasks to reduce the risk of falling. There are five family health tasks that must be considered, including being able to recognize family health problems, being able to make appropriate action decisions, being able to provide care to sick family members, being able to modify the environment, and being able to take advantage of public health service facilities. It can be concluded that after counseling the family and the elderly have understood the task of family health, once a day the family teaches tandem walking to the elderly to reduce the risk of falling in the elderly in Pentadio Timur Village, Gorontalo Regency